Alpelisib in the Treatment of Breast Cancer: A Short Review on the Emerging Clinical Data - Armaghani AJ (Dove Medical Press, 2020)
Avan J Armaghani, Hyo Sook Han Department of Breast Oncology, Moffitt McKinley Outpatient Center, H. Lee Moffitt Cancer Center and Research Institute, Tampa, FL 33612, USACorrespondence: Avan J Armaghani Email avan.armaghani@moffitt.orgAbstract: Hormone receptor positive, human epidermal growth factor receptor 2 negative (HR+/HER2 negative) breast cancer accounts for over 70% of all breast cancers. There has been much advancement in the treatment of HR+/HER2 negative metastatic breast cancer (MBC), in particular the development of more tailored and targeted therapies. Recently, greater understanding of the role of phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway in breast cancer has led to the development of PI3K inhibitors, which have proven to be effective in the treatment of HR+/HER2 negative MBC. In this review, we will discuss the role of the PI3K/AKT/mTOR pathway in breast cancer and therapies that have been developed to inhibit PI3K. We will discuss in detail the development of PI3K inhibitor alpelisib, indications for use in HR+/HER2 negative MBC, safety and tolerability and the future direction of this therapy in the treatment of breast cancer.Keywords: PI3K, PIK3CA, alpelisib